Work- and family-related variables, work–family conﬂict and women’s well-being: some observations - Noor, Noraini M. (Carfax Publishing, Taylor & Francis Group, 2003)

(untitled)
The present study was carried out to test an exploratory model consisting of three sets of variables (demographic, personality and work- and family-related variables) in the prediction of well-being. The model also provided a test of the indirect effect of these variables on well-being, via perceptions of work–family conﬂict. Both quantitative and qualitative analyses were used. In a sample of 147 employed British women with children, the results showed that these three sets of variables had both direct and indirect inﬂuence on well-being. Although work-related variables explained the most variance in the prediction of workinterfering-with-family conﬂict and job satisfaction, personality variables accounted for the most variance in the prediction of family-interfering-with-work conﬂict. Similarly, in the prediction of distress symptoms, demographic variables accounted for the most variance. The qualitative responses provided by the women complemented these ﬁndings. The proposed model appears to provide a better ﬁt of the complex relationships that may exist between the many variables encompassing women’s work and family lives than previous ones that have considered only one set of variables.